Distinct cholangiocarcinoma cell migration in 2D monolayer and 3D spheroid culture based on galectin-3 expression and localization - Sukphokkit, Siriwat; Kiatwuthinon, Pichamon; Kumkate, Supeecha; Janvilisri, Tavan (Frontiers in Oncology, 2023)
Cholangiocarcinoma (CCA) is difficult to cure due to its ineffective treatment and advanced stage diagnosis. Thoroughly mechanistic understandings of CCA pathogenesis crucially help improving the treatment success rates. Using three-dimensional (3D) cell culture platform offers several advantages over a traditional two-dimensional (2D) culture as it resembles more closely to in vivo tumor. Here, we aimed to establish the 3D CCA spheroids with lowly (KKU-100) and highly (KKU-213A) metastatic potentials to investigate the CCA migratory process and its EMT-associated galectin-3 in the 3D setting. Firstly, the growth of lowly metastatic KKU-100 cells was slower than highly metastatic KKU-213A cells in both 2D and 3D systems. Hollow formation was observed exclusively inside the KKU-213A spheroids, not in KKU-100. Additionally, the migration activity of KKU-213A cells was higher than that of KKU-100 cells in both 2D and 3D systems. Besides, altered expression of galectin-3 were observed across all CCA culture conditions with substantial relocalization from inside the 2D cells to the border of spheroids in the 3D system. Notably, the CCA migration was inversely proportional to the galectin-3 expression in the 3D culture, but not in the 2D setting. This suggests the contribution of culture platforms to the alternation of the CCA cell migration process. Thus, our data revealed that 3D culture of CCA cells was phenotypically distinct from 2D culture and pointed to the superiority of using the 3D culture model for examining the CCA cellular mechanisms, providing knowledges that are better correlated with CCA phenotypes in vivo.